2014
DOI: 10.2203/dose-response.13-019.bogen
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Models Fit to Ed001 Data on >40,000 Trout Exposed to Dibenzo[A,L]Pyrene Indicate Mutations Do Not Drive Increased Tumor Risk

Abstract: ᮀ ED 001 -study data on increased liver and stomach tumor risks in >40,000 trout fed dibenzo [a,l]pyrene (DBP), one of the most potently mutagenic chemical carcinogens known, provide the greatest low-dose dose-response resolution of any experimentally induced tumor data set to date. Although multistage somatic mutation/clonal-expansion cancer theory predicts that genotoxic carcinogens increase tumor risk in linear no-threshold proportion to dose at low doses, ED 001 tumor data curiously exhibit substantial low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A good MVK-model fit to HCC data from both groups of rats studied by Johnson et al 20 could be obtained when AFB 1 was assumed to increase HCC risk by a purely promotional (ie, nongenotoxic) mode of action (Table 1; Figure 3). A previous study 18 similarly reported that good MVK model fits to cancer bioassay data obtained after juvenile exposure to a potently mutagenic carcinogen could be obtained only if a purely promotional (nongenotoxic) mode of action was assumed. That study compared good MVK and ISM-like model fits to highly detailed dose–response data on incidence of liver and stomach tumors from the ED 001 study involving >40 000 trout exposed as juveniles to dibenzo[ a , l ]pyrene (DBP), the most potently mutagenic carcinogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good MVK-model fit to HCC data from both groups of rats studied by Johnson et al 20 could be obtained when AFB 1 was assumed to increase HCC risk by a purely promotional (ie, nongenotoxic) mode of action (Table 1; Figure 3). A previous study 18 similarly reported that good MVK model fits to cancer bioassay data obtained after juvenile exposure to a potently mutagenic carcinogen could be obtained only if a purely promotional (nongenotoxic) mode of action was assumed. That study compared good MVK and ISM-like model fits to highly detailed dose–response data on incidence of liver and stomach tumors from the ED 001 study involving >40 000 trout exposed as juveniles to dibenzo[ a , l ]pyrene (DBP), the most potently mutagenic carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…That study compared good MVK and ISM-like model fits to highly detailed dose–response data on incidence of liver and stomach tumors from the ED 001 study involving >40 000 trout exposed as juveniles to dibenzo[ a , l ]pyrene (DBP), the most potently mutagenic carcinogen. 18 Good MVK-model fits to cancer bioassay data obtained using parameter values that assume a purely nongenotoxic mode of action clearly are not biologically plausible for data involving exposure to highly potently mutagenic carcinogens such as AFB 1 and DPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(28) Doseresponse patterns exhibited for both DBP-induced tumor types were shown to be remarkably nonlinear and, when interpreted together with observations that DBP can induce adducts and mutations with approximate LNT dose-response in vivo, to provide evidence inconsistent with the current regulatory default assumption that mutations drive tumorigenesis. (29) These observations do not imply that MOA uncertainty concerning CC-induced cancer in any way reduces either concerns about susceptibility differences, or the importance of reflecting those concerns in protective applications of upper-bound risk estimates. Neither do they imply that in designing protective regulations required by statute, EPA should have any less flexibility than the Occupational Safety and Health Administration (OSHA) has under the U.S. Supreme Court's 1980 Benzene decision.…”
Section: Intent Bias and Conservatism Of Epa Estimates Of CC Potencmentioning
confidence: 92%
“…Previous studies addressing available data and mechanistic considerations highlight that Claims 1 and 2 are inconsistent with highly nonlinear or threshold‐like dose responses. Examples include: nasal epithelial cell proliferation and tumors induced in rats exposed by inhalation to formaldehyde, propylene oxide, or vinyl acetate; acetaminophen‐induced hepatic glutathione depletion and protein binding (which precede associated liver toxicity); serum‐enzyme alterations and mortality induced in rats dosed orally with vinylidene chloride; toxicity associated with excessive intake of certain nutrients or vitamins (e.g., manganese‐induced neurotoxicity, zinc‐induced toxicosis); hepatic GST‐P positive foci induction in Big Blue transgenic rats treated with the potently mutagenic heterocyclic amine, 2‐amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline (MeIQx); HGPRT mutations induced in AHH‐1 cells exposed to methyl methanesulfonate (MMS) or ethylene oxide, thyroid tumors in rodents administered perchlorate in drinking water; rodent liver and kidney tumors induced by chronic exposure to chloroform, leading to persistent cytotoxic and regenerative responses that indicate that “a mutagenic mode of action via DNA reactivity is not a significant component of the chloroform carcinogenic process”; liver and stomach tumors in >40,000 trout exposed to the highly potent (and in‐vivo linear) mutagen dibenzo[ a , l ]pyrene …”
Section: Introductionmentioning
confidence: 99%